2012
DOI: 10.7150/ijms.4637
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Pharmacogenetic-Based Warfarin-Dosing Algorithm in Patients of Han Nationality after Rheumatic Valve Replacement: A Randomized and Controlled Trial

Abstract: Background The polymorphisms of VKORC1 and CYP2C9 play increasingly important roles in the inter-individual variability in warfarin dose. This study aimed to evaluate the feasibility of clinical application of pharmacogenetic-based warfarin-dosing algorithm in patients of Han nationality with rheumatic heart disease after valve replacement in a randomized and controlled trial. Methods One hundred and one consecutive patients of Han nationality with rheumatic heart disease undergoing valve surgery were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 13 publications
2
51
1
3
Order By: Relevance
“…Actualmente hay estudios en diversas poblaciones que han demostrado una reducción de efectos adversos serios (40), una menor incidencia de anticoagulación excesiva (INR≥4) (9,40), un menor porcentaje de INR fuera del rango (40) e, incluso, la disminución del tiempo para alcanzar la dosis terapéutica con la consecuente reducción del riesgo de tromboembolia (9,40,41).…”
Section: Discussionunclassified
“…Actualmente hay estudios en diversas poblaciones que han demostrado una reducción de efectos adversos serios (40), una menor incidencia de anticoagulación excesiva (INR≥4) (9,40), un menor porcentaje de INR fuera del rango (40) e, incluso, la disminución del tiempo para alcanzar la dosis terapéutica con la consecuente reducción del riesgo de tromboembolia (9,40,41).…”
Section: Discussionunclassified
“…18,19,24,29,30 Th e pooled estimates of HRs ( Fig 4 ) showed that the GD resulted in signifi cantly shorter TMD (HR, Fig 5 ). Because of significant heterogeneity, we performed sensitivity analysis excluding the study with lowest Jadad score 29 …”
Section: Time To Maintenance Dosementioning
confidence: 95%
“…Of the 233 studies reviewed for eligibility, we extracted 54 studies for full-text review. We included a total of 10 studies [17][18][19][24][25][26][27][28][29][30] in qualitative and quantitative analysis (meta-analysis).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations